Color Masking Ability of Guided Enamel Regeneration with a Novel Self-Assembling Peptide and Resin Infiltration on Artificial Enamel Lesions Under Various Challenges: An In Vitro Spectrophotometric Analysis - Nassreen Albar; Syed Nahid Basheer; Mohammed M. Al Moaleem; Sana Ageel; Rehab Abbas; Rafaa Hakami; Arwa Daghrery; Mohammed Sawady; Syed Wali Peeran; Thilla Sekar Vinothkumar; Bassam Zidane (Biomimetics)
The color masking ability of resin infiltration (RI) and curodont repair fluoride plus–self-assembling peptide (CRFP-SAP) was investigated under various simulated oral challenging conditions. Sixty-four extracted caries-free human canines were randomly divided into two groups: Group 1 (RI) and Group 2 (CRFP-SAP). The baseline color values of samples were recorded using a spectrophotometer (VITA Easyshade® Advance 4.0 VITA Zahnfabrik, Bad Sackingen, Germany). The samples were stored in a demineralization solution for 4 days to induce artificial enamel lesions (AELs). The AELs of Groups I and II were treated with RI (Icon, DMG, Hamburg, Germany) and CRFP-SAP (vVARDIS, Zug, Switzerland), respectively, followed by color measurements. Each group was subjected to challenges such as remineralization, pH cycling, staining, and thermocycling, followed by color measurements. The difference between the mean ∆E (color difference value) of sound enamel and both treatment groups was less than 3.7 1-week post treatment. Meanwhile, the difference between the mean ∆E of RI-treated samples and all kinds of challenges was more than 3.7, while for the CRFP-SAP-treated samples, it was less than 3.7 for all kinds of challenges, except for the thermocycling, for which the mean ∆E difference was 4.3. RI and CRFP-SAP treatments were effective in masking the discoloration caused by AELs. However, the color was not stable for RI-treated samples, whereas it was stable for CRFP-SAP-treated samples under all challenges, except for thermocycling.